Radical Psychology: Multicultural and Social Justice Decolonization Initiatives - Gelberg, Susan O.; Poteet, Mathew A.; Moore, David D.; Coyhis, Don (Lexington Books, 2020)
Radical Psychology outlines the psychological factors that shape multicultural competency and social justice effectiveness, such as implicit and explicit biases, difficulties in accurate self-assessment of cultural competency and social justice skills, and the historical biases that continue to shape Western psychological training and practice. This book provides a challenging balance between research and professional reflections in order to appeal to readers with different cultural backgrounds and learning styles. The diversity of the contributors underscores the need to include cultural experts as side-by-side colleagues, consultants, and supervisors in order to help Western psychologists expand their professional cultural paradigms and worldviews. This book is recommended for psychologists, counselors, educators, researchers, social workers, substance abuse counselors, administrators, students, and mental health agencies.